Application of Effleurage Massage Technique in Postpartum Pain - Hidayati, Titi Aisyah; Mualifah, Laily; Riyana, Sri (Proceedings of the International Conference on Nursing and Health Sciences, 2024)
Data in the world around 80% of postpartum mothers give birth normally, in Indonesia mothers who give birth normally reach 81.5%, in Kulon Progo the number of mothers giving birth is 39.44%. Mothers who give birth normally often experience pain due to uterine contraception which is referred to as "after pain" is a pain that feels like heartburn that lasts for 1-4 days after giving birth The impact of pain if left untreated will cause inhibition of early mobilization, inhibition of lactation, inhibition of the bonding attachment process, Feelings of tiredness, anxiety, disappointment due to discomfort, disturbed sleep patterns, and even prolonged pain will increase the risk of postpartum blues. So that to reduce the pain, a non-pharmacological pain management intervention can be used in the form of effleurage massage techniques. Objective: this case study aims to determine the application of effleurage massage technique in postpartum pain. Method: This case study uses a descriptive method conducted in an approach with one respondent who will be carried out effleurage massage technique 2-3 times for 5 minutes for 3 days. Before and after the effleurage massage technique, the pain level was identified using a comparative pain scale. Results: There was a decrease in pain scale after being given the effleurage massage technique for 3 days from a pain scale of 4 (moderate pain) to 1 (mild pain). Conclusions: the effleurage massage technique is able to reduce the pain scale with an average pain scale in the range of 2 scales